Comparative efficacy of conventional and new rodenticides against Microtus arvalis (Pallas, 1778) in wheat and alfalfa crops - Jokić, Goran; Vukša, Petar; Vukša, Marina (Crop Protection, 2010)
In order to compare the efficacies of new rodenticides (sodium selenite and cellulose) and conventional ones (bromadiolone, brodifacoum and cholecalciferol) in controlling Microtus arvalis (Pallas, 1778) in wheat and alfalfa crops, experiments were conducted at two sites near Belgrade, Serbia, in the spring of 2008, using a standard EPPO method. The presence of rodent populations, their spatial distribution and density indexes were evaluated by pre-treatment census, and rodenticide efficacy by counting active holes 14 and 28 days after treatment. The average M. arvalis census numbers of 230/ha and 132/ha were found to cause 6.85% and 5.55% yield reduction in wheat, while the corresponding average counts of 285/ha and 253/ha caused 21.22% and 15.61% yield decrease in alfalfa crop. Twenty-eight days after treatment in wheat, the conventional rodenticides were found to reach average efficacy of 87% (bromadiolone), 95% (brodifacoum) and 82% (cholecalciferol), while the respective effectiveness in alfalfa was 81% (bromadiolone), 78% (cholecalciferol) and 95% (brodifacoum). Sodium selenite achieved 62% and 67% average efficacy in wheat and alfalfa, respectively, while cellulose reached the respective efficacies of 70% and 85%. Sodium selenite was less effective than either conventional rodenticides or cellulose. Repression M. arvalis with cellulose may significantly improve pest management programmes for rodent control in alfalfa crops.